Building Healthcare Sector in Post-Pandemic Era: Potential Role of Islamic Social Finance - Choiriyah, Evi Aninatin Ni’matul; Mubarak, Darihan; Indrawan , Imam Wahyudi (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
Islamic social finance instruments can be adopted to restore and achieve a healthy life and promote welfare after COVID-19, integrated with SDGs number three. As Islamic social finance instruments, Zakat, Infaq, Sadaqah, and Waqf play a significant role in solving marginalization and vulnerability that focus on local programs, thus impacting social and economic inclusion. Using a literature review approach, the objective of this paper is to examine the role of Islamic social finance instruments as alternative funding to achieve Sustainable Development Goals (SDGs) number three, "Good Health and Well-being," which is also in line with the recovery of COVID-19 in the healthcare sector. The results of this study indicate that Islamic Social Finance can solve the problem of economic funding due to the COVID-19 pandemic. In the short term, building and repairing primary health facilities, providing affordable health services, and providing access to health insurance for people experiencing poverty are actions that need to be realized immediately. As for the medium term, post-COVID-19, mental recovery and consultation efforts must be intensified. Investments in technology for telemedicine or telemedicine facilities and reforms in the post-pandemic COVID-19 health sector must be addressed and pursued. Based on current findings, this study recommends a synergy for all countries to jointly achieve the SDG number three target while restoring global socio-economic conditions post-COVID-19.